Partitioning Solvophobic and Dispersion Forces in Alkyl and Perfluoroalkyl Cohesion1. Issue 4 (20th November 2014) - Adam, Catherine; Yang, Lixu; Cockroft, Scott L.
Abstract Fluorocarbons often have distinct miscibility properties compared to their nonfluorinated analogues. These differences may be attributed to van der Waals dispersion forces or solvophobic effects, but their contributions are notoriously difficult to separate in molecular recognition processes. Here, molecular torsion balances were used to compare cohesive alkyl and perfluoroalkyl interactions in a range of solvents. A simple linear regression enabled the energetic partitioning of solvophobic and van der Waals forces in the self‐association of apolar chains. The contributions of dispersion interactions in apolar cohesion were found to be strongly attenuated in solution compared to the gas phase, but still play a major role in fluorous and organic solvents. In contrast, solvophobic effects were found to be dominant in driving the association of apolar chains in aqueous solution. The results are expected to assist the computational modelling of van der Waals forces in solution.